2017
DOI: 10.1016/j.amepre.2016.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Tuberculosis Treatment Completion by Incarceration Status, U.S., 1999–2011

Abstract: People diagnosed with TB disease at U.S. correctional facilities, especially the foreign born, require enhanced strategies for documenting TB treatment completion. Strengthened collaboration between correctional and public health agencies could improve continuity of care among released inmates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In this study, gender comparisons were not possible among prisoners and the general population because the prison registered male TB patients only in the whole study period. Similar studies globally have shown unevenly distributed high proportions of male prisoners than female prisoners ( [19,23,24]). Globally, there has been no universally accepted explanation to this disparity and most criminology studies point to the socialized gender roles and different expectationsof male and female behaviors [25].…”
Section: Discussionmentioning
confidence: 66%
“…In this study, gender comparisons were not possible among prisoners and the general population because the prison registered male TB patients only in the whole study period. Similar studies globally have shown unevenly distributed high proportions of male prisoners than female prisoners ( [19,23,24]). Globally, there has been no universally accepted explanation to this disparity and most criminology studies point to the socialized gender roles and different expectationsof male and female behaviors [25].…”
Section: Discussionmentioning
confidence: 66%
“…In this study, gender comparisons were not possible among prisoners and the general population because the prison registered male TB patients only in the whole study period. Similar studies globally have shown unevenly distributed high proportions of male prisoners than female prisoners( [20,24,25]). Globally, there has been no universally accepted explanation to this disparity and most criminology studies point to the socialized gender roles and different expectations of male and female behaviors [26].…”
Section: Discussionmentioning
confidence: 66%
“…In this study, gender comparisons were not possible among prisoners and the general population because the prison registered male TB patients only in the whole study period. Similar studies globally have shown unevenly distributed high proportions of male prisoners than female prisoners( [18,22,23]). Globally, there has been no universally accepted explanation to this disparity and most criminology studies point to the socialized gender roles and different expectations of male and female behaviours [24].…”
Section: Discussionmentioning
confidence: 66%